A First Human Case of Ocular Dirofilariosis due to Dirofilaria repens in Northeastern France. (12th January 2011) - Argy, Nicolas; Sabou, Marcela; Billing, Alain; Hermsdorff, Christian; Candolfi, Ermanno; Abou-Bacar, Ahmed
Abstract : We report the first case of ocular dirofilariasis to be diagnosed in northeast France (Alsace region), in a man who presented with a suborbital mass after a journey to Senegal. Microscopic examination of the surgical specimen identified Dirofilaria repens.